Choice of grafting options post apicectomy procedure by specialist endodontist: An original research - Singh, Harmeet; Mounika, Bangaru; Priya, Kalambur Perumal Lavanya; Tiwari, Heena Dixit; Rajesh, Damarasingu (International journal of health sciences, 2022)
Aim: The purpose of the present study was to evaluate the choice of grafting options post apicectomy procedure by various endodontists. Methodology: In the present descriptive survey, 8 questions were asked from 50 Endodontists, regarding the treatment options in cases of periapical pathologies as well as graft material preference after the apicoectomy procedure was performed. They were asked for usability, economics, long term healing of periapical region related with post apicoectomy graft placement. Results: 49.5% of participants preferred calcium hydroxyapatite as a graft material as compared to bone granules or PRP. It was also noted that radiographic resolution and improved trabecular pattern in peri-radicular area was the most important aspect that endodontists look into while looking at healing of periapical lesion (1.43 ±1.002). Most stable graft according to 61% of participants were autologous transplants- bone granules as well as calcium hydroxyapatite (1.422±1.02). Conclusion: Endodontists preferred calcium hydroxyapatite or bone grafts, which has more stable long-term results.